The philosophical framework of LGBT-inclusive education bases, policies, and practices - Callueng, Eva Aurora D. (College of Education, University of the Philippines Diliman, 2016)
The inclusion of lesbian, gay, bisexual, transgender (LGBT) experiences and issues in the curriculum was examined in order to know if it contributes to having a holistic education. By looking at the philosophical bases of education, the study analyzed whether the current curriculum includes the experiences of LGBT people concerning their sexual orientation, gender identity and expression (SOGIE). The particular learning areas or subjects where SOGIE-related issues maybe included were also examined. The common concepts held by the students, teachers, and administrators were used for the descriptive analysis on LGBT-inclusive education through a survey method. In the document analysis, information pertaining to LGBT-inclusive education was analyzed and noted in the participant observation method that was employed. The nature and source of the common concepts held by students, teachers, and administrators against lesbians, gays, bisexuals, and transgender people (LGBT) suggest discrimination and bias. It also revealed dearth of literature and studies in education while the implementation of philosophical framework is lacking in force. Policies and practices in education showed a gap between the intended and the implemented curriculum. Confusions and varying notions about the nature of SOGIE result in stereotyping and discriminations. Thus, an educational framework that is LGBT-inclusive is necessary to address the problems brought about by a form of education that excludes LGBT people.